2015
DOI: 10.1002/prep.201500011
|View full text |Cite
|
Sign up to set email alerts
|

A New Reference Material and Safe Sampling of Terrorists Peroxide Explosives by a Non‐Volatile Matrix

Abstract: [a] 1IntroductionThe increasing threat of worldwide terrorism results in ag rowing necessity of security protocols for public transport, buildings, or major events [ 1].E specially aircrafts,r ailway systems, large vessels, administrational buildings, and military bases face as ignificant threat [2].M ostly,t he exact details of an incident do not reach public knowledge, but it is known that often improvised explosive devicesw ith peroxide-based explosives were involved [3].T he most prominent compounds amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…Both peroxides are extremely sensitive toward friction. [13] The sensitivity values for TATP are slightly higher than the values stated by Lubczyk et al [7], yet the friction sensitivity measured in this work is at the lower limit of the measurement range of the testing device used (5 N). Both compounds have 200 mJ sensitivity toward electrostatic discharge.…”
Section: Polymorphism Of Tatpcontrasting
confidence: 49%
See 1 more Smart Citation
“…Both peroxides are extremely sensitive toward friction. [13] The sensitivity values for TATP are slightly higher than the values stated by Lubczyk et al [7], yet the friction sensitivity measured in this work is at the lower limit of the measurement range of the testing device used (5 N). Both compounds have 200 mJ sensitivity toward electrostatic discharge.…”
Section: Polymorphism Of Tatpcontrasting
confidence: 49%
“…Oxley et al investigated the factors influencing the formation of TATP 1 and its side product diacetone diperoxide (DADP, 2) [5] as well as the destruction of TATP [6]. Lubczyk et al [7] recently published a method for desensitizing TATP for training and testing purposes in an ionic liquid matrix and pointed out that resublimed TATP 1 shows a higher impact (0.1 J) and friction sensitivity of (0.05 N) than the crude product from the aqueous synthesis (0.5 J, 0.2 N) that is stabilized by trace amounts of water. The resublimation of TATP during storage enhances the risk of unintended detonation.…”
Section: Introductionmentioning
confidence: 99%
“…Waldvogel et al, showed that highly sensitive peroxide based explosives can be dissolved in ionic liquids for a safe handling [45]. Dissolving peroxide explosives such as TATP in lipophilic ionic liquids gives rise to novel and easy to use simulants of as authentic compounds.…”
Section: Hexamethylene Triperoxide Diamine (Hmtd)mentioning
confidence: 99%
“…Moreover, the stabilizing effect of the ionic liquids can be exploited for a safe sampling of large quantities of these explosives. Such samples of triacetone triperoxide are long-term stable, safe, and valid for forensic evaluations [45]. Solutions of 2% TATP in 1-methyl-3-octylimidazolium tetrafluoroborate can serve as powerful odor sources, which can simulate large quantities of TATP.…”
Section: Hexamethylene Triperoxide Diamine (Hmtd)mentioning
confidence: 99%
“…With respect to its high vapor pressure and extreme sensitivity towards impact and friction, the explosive neither finds military nor civil application. Dry TATP is reported to have a higher impact (0.1 J) and friction sensitivity (0.05 N) than the crude product from the aqueous synthesis (0.5 J, 0.2 N) that is stabilized by trace amounts of water [2]. Despite that, the compound is a homemade explosive that is illegally synthesized by both amateur chemists and terrorists, which is reflected by numerous incidents [3][4][5].…”
Section: Introductionmentioning
confidence: 99%